A novel view on lubricant flow undergoing cavitation in sintered journal bearings. (August 2015) - Scheichl, Bernhard; Neacşu, Ioana Adina; Kluwick, Alfred
Abstract: A new rational formulation of the cavitation phenomenon occurring in porous journal bearings in the regime of fully hydrodynamic lubrication is presented. The suitably extended form of the Reynolds equation is coupled with the semi-phenomenological Darcy׳s law so as to yield a proper description of the combined flow through the lubrication gap and the porous (sintered) seat, respectively. It is found that the initially unknown boundaries of cavitation give inevitably rise to gradual steepenings of the pressure gradients and the saturation of the lubricant at recondensation that finally form up to localised discontinuities. Hence, it is focussed on both theoretical foundations and an elaborate numerical investigation of the resultant lubrication problem. In order to determine the limits of applicability of this approach, specific investigations aim at evaluating the extreme cases of relatively low and high bearing loads, i.e. ε → 0 and ε → 1 _ where ε is the eccentricity ratio, and very long/short as well as highly porous/(almost) massive bearings. Here the effort is seen to be reduced by considering appropriate distinguished limits. The results include values of the friction coefficient obtained for various configurations and, most interestingly, point to a threshold value of ε above which the loss of numerical solutions indicates the loss of steady-state operation of the bearing. A first validation by in-house experiments proves satisfactory. Abstract : Graphical abstract: Abstract : Author-Highlights: We present a rigorous theory of self-sustained lubrication of porous journal bearings. It resorts to homogenisation of creeping flow through media having a micro-structure. The new numerical method copes directly with cavitation under steady-state operation. Varying the independent dimensionless groups yields a systematic theoretical analysis. Special emphasis is placed on spontaneous recondensation and the associated jump conditions.